Hubungan Peran Pengawasan Orang Tua Dan Kecanduan Gadget Dengan Kemampuan Interaksi Sosial Pada Anak Usia Sekolah di SD Negeri 1 Pamijen Sokaraja - Ayunda Ragil, Dyana Ratih; Sodikin, Sodikin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: To determine the correlation between the role of parental supervision and gadget addiction with the ability of social interaction in school-age children in SD Negeri 1 Pamijen Sokaraja.Â ABSTRACTMethod: It was a quantitative study by using descriptive correlative with a cross-sectional study design. The populations were the students in grades 4, 5, and 6 of SD Negeri 1 Pamijen Sokaraja. The total samples were 46 students. They were collected by using a cluster sampling technique. The data were collected by using a questionnaire. The data were analyzed using the Chi-square test.Â Results: The analysis showed that the role of parental supervision was related to the ability of social interaction with a p-value of 0.000 and the gadget addiction was related to the ability of social interaction with a p-value of 0.012.Â Conclusion: There was a relationship between the role of parental supervision and gadget addiction with the ability of social interaction in school-age children in SD Negeri 1 Pamijen Sokaraja.